A high sensitivity and selectivity n-butanol sensor based on monodispersed Pd-doped SnO2 nanoparticles mediated by glucose carbonization. (10th August 2020) - Yao, Zhiqiang; Wang, Xi; Yang, Man; Ma, He; Sun, Yanfeng; Zhang, Hong; Dong, Tianwei; Liu, Weifeng
Abstract: Doping of noble metals into semiconductors is often used to enhance the response of gas sensors, accompanying the decrease of the particle size. In this work, pure and palladium-doped dispersive nanoscale tin dioxide nanoparticles with abundant surface defects are synthesized efficiently via a facile hydrothermal method. In the experiment, glucose is used as the carbon source to limit the growth of crystals through the carbonization process and create abundant surface defects after high temperature calcination. Compared with pure SnO2, Pd doping only slightly decreases the particle size with the increase of palladium doping amount from 11.9 nm to 9.6 nm. A gas-sensing investigation indicates that the sensor devices based on pure and 1 at%, 3 at%, 5 at% palladium-doped SnO2 show an obvious high response to n-butanol. In particular, the response to n-butanol reaches to the maximum with the palladium doping amount of 3 at%, and the response increases from 33.3 to 92.9 to 100 ppm n-butanol compared with pristine SnO2 nanoparticle at optimal working temperatures. A gas-sensing mechanism related to surface defects, chemical and electrical sensitization is also discussed.